Comparison of void fraction measurements using different techniques in two-phase flow bubble column reactors. (May 2018) - Hernandez-Alvarado, Freddy; Kleinbart, Simon; Kalaga, Dinesh V.; Banerjee, Sanjoy; Joshi, Jyeshtharaj B.; Kawaji, Masahiro
Highlights: Local, area and volume average void fraction measurements have been made using different methods. Two-phase flow measurements were performed in a batch bubble column, co-current up-flow and counter-current down-flow with relatively large bubbles and micro-bubbles. Measurement accuracy has been found to depend significantly on the mode of two-phase flow operation and bubbles sizes. The advantages and limitations of different methods are reported. Abstract: Local, area and volume average void fraction measurements have been conducted in gas-liquid two-phase flow through vertical pipes of different diameters under different modes of operation covering up-flow, down-flow and batch bubble column. The measurement techniques used include gamma ray densitometry, electrical resistance tomography (ERT), wire mesh sensor (WMS), optical void probe, and pressure transducers. The consistency among different measurement techniques has been examined by comparing the local, area and volume-average void fraction measurements made using the above methods in the same test section under the same flow conditions. The accuracy of the measurement techniques has been found to depend significantly on the mode of two-phase flow operation. The results show that the gamma densitometry and the pressure transducers can produce highly reliable measurements independent of the mode of operation. However, the optical void probe was found to underestimate the local values of void fractions, particularly, in the case of a co-current down-flow with sub-millimeter sized bubbles. Also, the electrical resistance tomography technique was found to be the least reliable method, as it underestimated the void fraction in the co-current up-flow as well as co-current down-flow operation. The accuracy of the wire mesh sensor was strongly dependent on the size of the bubbles relative to the wire mesh spacing.